Put down your phone and listen to me: How boss phubbing undermines the psychological conditions necessary for employee engagement - Roberts, James A.; David, Meredith E. (Computers in human behavior, 2017)
This study investigates the impact of an increasingly common behavior by supervisors, namely boss phubbing (phone-snubbing). We define boss phubbing (BPhubbing) as the extent to which a supervisor uses or is distracted by his/her cell phone while in the presence of subordinates, and examine its impact on supervisory trust and the psychological conditions necessary for employee engagement. Three studies were conducted to test the research hypotheses, using both a continuous measure and a situational prime of BPhubbing. The results reveal that BPhubbing has a negative indirect effect on employee engagement. Specifically, BPhubbing reduces employee engagement by undermining supervisory trust which, in turn, lowers employee engagement via the psychological conditions of meaningfulness and availability. This research offers both theoretical and practical implications regarding how smartphone use, and BPhubbing in particular, may undermine job-related outcomes. The results provide a rich theoretical understanding of the psychological processes through which BPhubbing impacts employee engagement. The findings suggest a need for supervisory training and clear corporate policies regarding smartphone use. •A nine-item boss phubbing (Phone snubbing) scale is introduced.•Boss phubbing undermines supervisory trust.•Lack of supervisory trust lowers employee engagement.•Boss phubbing has a negative indirect effect on employee engagement.•Kahn's psychological conditions mediate the trust – engagement relationship.